Legal analysis of the Case of helped 13 children live in a cave Legal Analysis: Case study on the 13 Children Trapped in Thum Luang Cave - wittayakiatlert, Kanchanarat (Journal of Humanities and Social Sciences Loei Rajabhat University, 2018)
This academic article, entitled “Legal analysis of the case of the rescue of 13 Children trapped in a Tham Luang cave”, aimed at analyzing the laws that have been controversial and criticizing issues including: (1) The law about cave penetration, groundwater drilling, tree cutting, ground digging and anything activities done in the park, (2) the law on doing facebook live, taking photos and video and etc. in the park, (3) the law relating to the use of drone, the pilotless aircraft, (4) the laws on getting permission for a park visit, and (5) the law on compensation for those who were affected by damage caused by any activities done to remedy the disasters, especially the farmers whose rice fields were damaged by the water drained from the cave. Framework for analysis included (1) National Forest Act 1964, (2) Forest Act BE 2484, (3) Criminal Code, Section 67, (4) Prevention and Mitigation Act, BE 2550, and (5) The Radio Communication Act BE 2498, as amended. The results showed that The law that can be enforced under the approval of the governor under the Prevention and Mitigation Act BE 2550 included (1) The law of cave penetration, groundwater drilling, tree cutting, ground digging and anything activities done in the park, (2) the law on doing facebook live, taking photos and video and etc. in the park, (3) the law relating to the use of drone, the pilotless aircraft. If it is done according to the authority, such action shall be exempted from the offense and liability under Section 43. According to the law on getting permission for a park visit, it states that anyone can visit the park for recreation with free of charge, according to the National Forest Act 1964 and the Forest Act 1941. In terms of the law on compensation for those who were affected by damage caused by any activities done to remedy the disasters, especially the farmers whose rice field were damaged by the water drained from the cave, the government agency had compensated and complied under Section 43 of the Disaster Prevention and Mitigation Act, BE 2550.